If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7h + 3h + -4h + -3 = 0 Reorder the terms: -3 + -7h + 3h + -4h = 0 Combine like terms: -7h + 3h = -4h -3 + -4h + -4h = 0 Combine like terms: -4h + -4h = -8h -3 + -8h = 0 Solving -3 + -8h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -8h = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -8h = 0 + 3 -8h = 0 + 3 Combine like terms: 0 + 3 = 3 -8h = 3 Divide each side by '-8'. h = -0.375 Simplifying h = -0.375
| 7b-(6+b)=-22 | | 9d+8-5d-3= | | 3x/4-1/2=5/3 | | (9x+8)+12=(8x+8)+10 | | u-8=-3 | | .95x+.05(2-x)=.10(109) | | 3b-(6+b)=-22 | | 25x+19=3(7x+7)+4x-2 | | 7-10=8+x+7 | | 63=2-5x | | 6b+9=3a | | 3(x-2)+3=x+5(x+3)-3x | | 4b+12(x-1)=36 | | 5.7/17.1=19.2/x | | 5x/a+9x/c=b | | 8(p)-24=-4(1-3)(p) | | 5.7/17.1=19.2 | | w/5+1= | | 3(g-8)=18 | | 6x-3(3x+2)=6 | | 5j+20+8j=-36 | | -3(n-14)=-9 | | 2.5t-5=x | | -2(7-t)+4=-4 | | x^2+9x=-110 | | -4(1+8x)+7x(7x-3)=0 | | 10-1d=-34-5d | | (x+1)(y-2)= | | -(m+-9)=-2 | | -4.9x^2+280x+115=0 | | Y=-1/2x^2+3/2x+3 | | -28+6p=70 |